UiTM networking visit & collaboration meeting in Australia - UiTM, UiTM Global (Office of International Affairs (OIA), 2023)
Universiti Teknologi MARA (UiTM), represented by UiTM Global, began negotiations with six Australian universities during an official visit to Australia from August 26 to September 1, 2023, to explore and strengthen strategic cooperation in the internationalization agenda of higher education. The focus of the negotiations was to establish cooperation and collaboration by offering interdisciplinary academic programs, including short-term courses and microcredential programs, enhancing translational research development, improving student exchange programs with universities listed in the top 300 QS World University Rankings, and maximizing international cooperation in various aspects. The negotiations in Australia involved the University of Melbourne, Swinburne University of Technology, Deakin University, Macquarie University, the University of Sydney, and the University of Technology Sydney. Additionally, the UiTM delegation held discussions on UiTM's internationalization strategy with the Consulate General of Malaysia in Melbourne and Education Malaysia Australia. These visits and networking discussions are also part of UITM's efforts to become a Globally Renowned University by 2025. The UiTM delegation to Australia was led by the Assistant Vice-Chancellor (Internationalization), Prof. Dr. Shahriman Zainal Abidin. The UiTM delegation also had the opportunity to hold discussions with Imam Shahl Alsuleimen, President of the Australian National Imams Council (ANIC) and United Muslims of Australla (UMA), regarding research collaboration in the field of HALAL and current issues concerning the Muslim community in Australia.